Assessing the influence of inbound logistics on company performance: a case of Browncast steel company (Pvt) Ltd. - Nyereyemhuka, Omega (Midlands State University, 2017)
The research study is about inbound logistics on company perfomance. The researcher aimed at determining the influence of Logistics Information management on lead time, assessment on the effects of inventory management policies on reducing stock outs, influence of transport system should be used on product delivery and inventory costs that are incurred and affects profitability of the company. The research was carried out at Browncast steel merchant company a member of steel merchant in Zimbabwe Steel Industry. Major arguments highlighted issues on the influence of inventory costs shows that some cost of capital tied up should be used for other purposes, information, materials and inventory should flow from the steel supplier in a less cost and faster way. The research relied on descriptive research design aided by exploratory design. A sample size of 82 respondents was used, 24 employees and 58 steel suppliers. An average questionnaire response rate of 87% was achieved. Interviews were also administered to top management. Both probability and non-probability sampling to achieve unbiased results. Both primary and secondary data was from inbound logistics textbooks, interviews, questionnaires, company financial reports enabling validity of the research. Major findings concludes that storage space costs influence inventory costs on company profitability and unutilized space maybe rented out. The use of 3 to 4 tonnes sizes of delivery trucks proved small as they determine the influence of transport therefore 5 tonne trucks may be used, information technologies facilities like internet should be adopted for quick movement of information and maximize inventory postponement policy.